Beggar Thy Neighbor : The Case of the Czech Republic - Horák, Petr (2018)
This thesis examines if there exists beggar thy neighbor effect of innovations to fiscal and monetary policy in the context of the Czech economy. I developed two structural VAR models identified by sign restriction and based on data from 1999Q1 to 2017Q2. The first model investigates how different innovations to fiscal and monetary policy originating in Germany affect the German economy, and how these effects are transmitted to the Czech economy. The second model investigates how different innovations to fiscal and monetary policy originating in the Czech Republic affect the Czech economy, and how these effects are transmitted to the Slovakian economy. The effects of a particular shock are similar in both models. I find that government expenditure shocks have beggar thyself effect and not beggar thy neighbor effect. Further, I find that tax cut shocks have both beggar thyself effect and beggar thy neighbor effect. The only fiscal shock with a positive effect on the domestic economy is the balanced budget restrictive shock. Monetary policy shocks have a slight beggar thy neighbor effect and and mostly a slight help thyself effect.